"A little bit of everything?" Conceptualising performance measurement in hybrid public sector organisations through a literature review. Issue 3 (12th March 2021) - De Waele, Lode; Polzer, Tobias; van Witteloostuijn, Arjen; Berghman, Liselore
Abstract : Purpose: Numerous of today's public sector organisations (PSOs) can be characterised as hybrids. Hybridity is caused by different (at times conflicting) demands that stem from the institutional environment, which is likely to affect performance measurement in these organisations. This paper focuses on the relationship between hybridity and organisational performance, which has so far not been studied in detail. Design/methodology/approach: Based on a literature review (final sample of 56 articles), the authors systematise performance dimensions alongside the pillars "economy", "efficiency", "effectiveness" and "(social) equity". The article summarises results in a framework for measuring performance in hybrid PSOs. The authors outline strategies as to how public managers can tailor frameworks to the requirements and idiosyncrasies of organisations. Findings: Since hybrid PSOs combine logics from different administrative models (Weberian bureaucracy, market-capitalism and democracy), so need their organisational performance measurement systems. Potential synergies from and frictions between the different performance dimensions related to the four pillars are discussed. Originality/value: This is the first literature review on performance dimensions and their application in hybrid PSOs. The distilled "hybrid performance measurement framework" can be scrutinised and further refined in future research.